Flow behaviour of liquid crystalline phases of branched chain glycolipids / Azwa Amanina Mislan - Azwa Amanina , Mislan (2019)
Increase in environmental awareness has led to the demand of alternatives for the commercially available chemical surfactant. Glycolipids, being low toxicity, biodegradable and showing surface activity have became one of the candidate for alternatives which known as biosurfactants. In this study, glucose and maltose are attached to the Guerbet alcohol; 2-hexyl-1-decanol through glycosidic linkage to form branched chain glycolipid namely 2-hexyl-decyl-β-D-glucoside (β-Glc-C10C6) and 2-hexyl-decyl-β-D-maltoside (β-Mal-C10C6) respectively. The effect of different head group size on the thermotropic and lyotropic mesophases was investigated. The mesophases were determined by optical polarizing microscopy and small angle X-ray scattering. β-Mal-C10C6 only shows lamellar (Lα) phase in both conditions. The shear viscosity test indicates all mesophases in thermotropic and lyotropic conditions exhibits shear thinning behaviour. All rheological measurements were obtained in the linear viscoelastic regime. In general, the viscoelastic studies on thermotropic A rheometer was used to investigate the flow behaviour of β-Glc-C10C6 that exhibits inverse hexagonal phase (H2) and inverse bicontinuous cubic phases (Ia3d and Pn3m) in thermotropic and lyotropic conditions respectively. H2 (β-Glc-C10C6) and Lα (β-Mal-C10C6) phases show that G’ and G” increase with the frequency indicating the typical viscoelastic response for non-Newtonian fluid at the selected temperatures. The lyotropic inverse bicontinuous cubic of β-Glc-C10C6 containing different water concentrations shows the dominance of G’ over G” at the range of frequency and temperature tested. A similar finding was observed for lyotropic Lα phase of β-Mal-C10C6 but with a lower magnitude of structural strength.